2012
DOI: 10.2139/ssrn.2180022
|View full text |Cite
|
Sign up to set email alerts
|

Are CDS Spreads Predictable? An Analysis of Linear and Non-Linear Forecasting Models

Abstract: This paper investigates the forecasting performance for CDS spreads of both linear and non-linear models by analysing the iTraxx Europe index during the financial crisis period which began in mid-2007. The statistical and economic significance of the models' forecasts are evaluated by employing various metrics and trading strategies, respectively. Although these models provide good in-sample performances, we find that the non-linear Markov switching models underperform linear models out-of-sample. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Also the results of Naifar (2011b) that CDS indices behave as high-risk indicator during the crisis period and become more sensitive to stock market conditions and macroeconomic variables are confirmed. As the latest study by Avino and Nneji (2014) show, our results point out to the possible market inefficiency of CDS index market with focus on financial sector.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Also the results of Naifar (2011b) that CDS indices behave as high-risk indicator during the crisis period and become more sensitive to stock market conditions and macroeconomic variables are confirmed. As the latest study by Avino and Nneji (2014) show, our results point out to the possible market inefficiency of CDS index market with focus on financial sector.…”
Section: Resultssupporting
confidence: 62%
“…The latest paper by Avino and Nneji (2014) investigates the forecasting performance for CDS spreads of both linear and non-linear models using daily quotes of iTraxx Europe CDS indices for the period from September 2005 to September 2010. They found that linear models often outperform Markov switching models, but the findings raise some doubts on the efficiency of the European CDS index market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…21 Avino and Nneji (2014) find that the prediction of CDS spreads by an AR(1) is not improved by adding exogenous variables.…”
Section: Robustnessmentioning
confidence: 95%
“…There is no improvement in the forecasting power of the VAR by including exogeneous variables, see also Avino and Nneji (2014) 21 . We consider several exogenous variables that are generally used in the literature to control for common changes among the CDS spreads (as in Alter and Beyer (2014) individually we find that none of them are significant for CDS spreads and only the change of the Euribor is significant for bond yield spreads.…”
Section: Robustnessmentioning
confidence: 99%
“…Hence the existence of predictable thus stationary paths for CDS spreads is an interesting research area which is important for asset pricing and credit portfolio management. Moreover, as Avino and Nneji (2014) assert, although there is a substantial literature regarding the stationarity of equity, bond and foreign exchange markets, the stationarity of CDS spreads is quite understudied.…”
Section: Introductionmentioning
confidence: 99%